Santidade na pós-modernidade: uma leitura contemporânea da Lumen Gentium à luz de Francisco de Sales - Costa Junior, Agnaldo (2023)
A double matrix is required to read this work. It is a study of Christian holiness as defined by Vatican Council II, with the goal of contributing to the rediscovery of Francisco Sales' mystical spirituality. The life and work of the Bishop of Geneva, although known, are still little studied in Brazil. His thoughts, in the scope of academic studies, are still restricted to the European environment. The purpose of this work is to demonstrate the unique nature of the relationship between the fifth chapter of Lumen Gentium and Salesianity in preparation for a dialogue with postmodernity. Therefore, the study of Christian holiness within a contemporary reading of Lumen Gentium in the light of Francisco de Sales is what is conceived as being the object of Christian spirituality. In the framework of this broad parameter, it is necessary to establish that the legacy of the Bishop of Geneva, who did not shy away from the dialogue with the contemporary world, insists on the primacy of love. In this way, the ecclesial life "proceeds from love, is rooted in love, tends to love, and lives from love." And in this regard, the spiritual life is based on God’s image, enabling ecumenical and interreligious dialogue in such a way that the vertical deepening of spirituality widens the horizontal edges of the integration of all human affectivity in Christian holiness: God is the God of the human heart